Heat and Water Vapour Transfer Trough the Envelope of a Cold chamber - Clito Afonso (2016)
The diffusion of water vapour in the atmospheric air through the elements of the envelope of a cold storage room, causedby the pressure gradient between the external and internal environment is inevitable in most situations. In fact, if the conditions in theinterior of an envelope element are such as to enable the vapour freezing of the migrant water, the increase in volume from theformation of ice will causes the deformation of this element with very serious consequences, which can go up to its partial or totaldestruction. In this scenario, readily note the importance of vapour barriers associated with a properly designed insulation, tend to notonly reduce the amount of water diffused, but also prevent the achievement of the conditions for freeze inside the engaging elements.The purpose of this work is to formulate the procedure for design of vapour barriers connected with the design of optimized thermalinsulation, and then apply it to a cold chamber located in Portugal. Vapour barriers and the procedure for its design are bothmandatory. The required thickness of the vapour barrier is relatively small, and the most appropriate insolation (maintaining theoptimal thickness) is the black cork agglomerate.